Circulating T Cells Exhibit Different TIM3/Galectin-9 Expression in Patients with Obesity and Obesity-Related Diabetes - Lili Sun; Shengyi Zou; Sisi Ding; Xuan Du; Yu Shen; Cuiping Liu; Bimin Shi; Xueguang Zhang (Journal of Diabetes Research)
Aims. Obesity is highly associated with type 2 diabetes mellitus (T2DM). The TIM3/galectin-9 pathway plays an important role in immune tolerance. Herein, we aimed to investigate the expression of TIM3 and galectin-9 in peripheral blood and to evaluate their clinical significance in patients with obesity and obesity-related T2DM. Methods. We performed flow cytometry on peripheral blood samples from healthy donors (HC), patients with simple obesity (OB), and patients with obesity comorbid T2DM (OD). The expression of TIM3 on CD3+, CD4+, and CD8+ T cells was determined. The level of galectin-9 in plasma was detected by ELISA. Results. We demonstrated the enhancement of TIM3 on CD3+, CD4+, and CD8+ T cells in the OB group when compared with healthy controls, while it was decreased significantly in the OD group. The TIM3+CD8+ T cells of the OB group were positively correlated with risk factors including BMI, body fat rate, and hipline. The concentration of galectin-9 of the OD group in plasma was significantly higher than that of healthy donors and the OB group. Moreover, the level of galectin-9 of the OD group was positively correlated with fasting insulin and C-peptide, which were two clinical features that represented pancreatic islet function in T2DM. Conclusions. Our results suggested that TIM3 and galectin-9 may be potential biomarkers related to the pathogenesis of obesity-related T2DM.